Phytochemical and Antioxidant Test of Binahong (Anredera cordifolia (Tenore) Steenis) Leaves Ethanol Extract - Fensia Analda Souhoka; Imanuel Berly Delvis Kapelle; Elisabeth Sihasale (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Binahong Anredera cordifolia (Tenore) Steenis leaves contain chemical compounds that can be used as antioxidants. This study aims to examine the phytochemical and antioxidant activity of the ethanol extract of binahong leaves. Binahong leaves were extracted using the maceration method with an ethanol solvent. The phytochemical test showed that the ethanol extract of binahong leaves contained phenolic compounds, flavonoids, alkaloids, and tannins to have potential antioxidants. The antioxidant activity test was carried out using the DPPH method and absorbance measurement with a UV-Vis spectrophotometer at a wavelength of 517 nm. The results showed that the ethanol extract of binahong leaves had strong antioxidant activity, as evidenced by the IC50 value of 87.423 Ã‚Âµg/mL.